Role of Circular RNA in Kidney-Related Diseases - Chen, Xin-Tian; Li, Zhong-Wei; Zhao, Xue; Li, Min-Le; Hou, Ping-Fu; Chu, Su-Fang; Zheng, Jun-Nian; Bai, Jin (Frontiers in Pharmacology, 2021)
The kidney is vital in maintaining fluid, electrolyte, and acid–base balance. Kidney-related diseases, which are an increasing public health issue, can happen to people of any age and at any time. Studies have shown that various kidney diseases, including renal cell carcinoma, acute kidney injury, and chronic kidney disease, are linked to circular RNAs (circRNAs). circRNAs are endogenous RNA that are produced by selective RNA splicing and are involved in progression of various diseases. This review outlines the characteristics and biological functions of circRNAs and discusses specific studies that provide insights into the function and potential of circRNAs for application in the diagnosis and treatment of kidney-related diseases.